Improvement of Mixing Efficiency in the Combustion Chamber of a Powder-Fuel Ramjet Engine - Xi, Wenxiong; Liu, Jian; Mengfei, Ren (Frontiers in Energy Research, 2021)
The challenge of the powder-fuel ramjet is to improve the mixing effect of powder-fuel with oxidizing agents and combustion efficiency. To improve the mixing and combustion efficiency of the powder-fuel ramjet engine, three configurations in head shapes and three exhaust gas inlet patterns of the engine are designed based on a typical powder-fuel ramjet engine combustion chamber. The effect of the head shapes and exhaust gas inlet patterns is analyzed and compared by the three-dimensional numerical simulation method. A comprehensive model validation is built, and the calculation results of the k-ε standard model are compared with the experimental data. The results show that the cylindrical head forms a recirculation zone at the head of the combustion chamber, which leads to powder deposition in the head region of the chamber. The design with the round head and the coned head reduces the recirculation inside the head region, and the exhaust gas from the fuel gas generator has benefits in powder injection and mixing inside the combustion chamber. The exhaust gas inlet of the inclined six hole type has benefits in the mixing of powder and high temperature exhaust gas because it generates strong flow impingement in the core part of the chamber.